"A gift from God": Anglo-Greek relations during the dictatorship of the Greek colonels - Nafpliotis, Alexandros (The Historical Review/La Revue Historique, 2014)
The focus of this article is an analysis of the Greek junta’s relations with the Wilson and Heath governments in the United Kingdom from 1967 to 1974. Emphasis is placed on diplomatic relations between the two traditional allies. The reactions of the military leaders of the regime in Athens and its representatives in Britain to policies pursued by London towards the establishment, consolidation and eventual demise of the colonels’ dictatorship are presented through the examination (for the first time) of official documents from both the UK and Greece. It is argued that the Greek military regime struggled to cultivate relations with Britain primarily for reasons of domestic and international prestige. Whereas Whitehall pursued a policy of “good working relations” with the junta in order to promote British interests vis-à-vis NATO, Cyprus and trade, the leadership in Athens was solely interested in using British support to gain legitimacy internationally and domestically.